Method for producing solid electrolytes

JP2026167625APending Publication Date: 2026-10-14NITERRA CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2026056628
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-04-01
Filing Date
2026-03-30
Publication Date
2026-10-14

Smart Images

  • Figure 2026167625000001_ABST
    Figure 2026167625000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing solid electrolytes that can reduce energy consumption during sintering. [Solution] A method for producing a solid electrolyte having a garnet-type crystalline structure containing Li, La, Zr, and O includes a calcination step of heating raw material powders to synthesize a solid electrolyte, wherein the raw material powders have a wavenumber of 3700 ± 10 cm² when their infrared absorption spectrum is measured by total internal reflection. -1 The absorbance of the peak appearing in this range divided by the absorbance of the peak originating from the OH group of lanthanum hydroxide is 0.02 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a method for producing a solid electrolyte having a garnet-type crystalline structure containing Li, La, Zr, and O. [Background technology]

[0002] Prior art for synthesizing a solid electrolyte having a garnet-type crystalline structure containing Li, La, Zr, and O by heating raw material powders and performing solid-phase sintering is disclosed in Patent Document 1. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2013-32259 [Overview of the project] [Problems that the invention aims to solve]

[0004] Prior art requires techniques to reduce energy consumption during sintering.

[0005] This invention was made to meet this requirement and aims to provide a method for manufacturing solid electrolytes that can reduce energy consumption during sintering. [Means for solving the problem]

[0006] A first embodiment for achieving this objective is a method for producing a solid electrolyte having a garnet-type crystalline structure containing Li, La, Zr, and O, comprising a calcination step of heating raw material powders to synthesize a solid electrolyte, wherein the raw material powders have a wavenumber of 3700 ± 10 cm² when their infrared absorption spectrum is measured by total internal reflection. -1 The absorbance of the peak appearing in this range divided by the absorbance of the peak originating from the OH group of lanthanum hydroxide is 0.02 or greater.

[0007] In the second embodiment, in the first embodiment, the maximum temperature at which the raw material powder is heated in the calcination process is between a temperature 10°C lower than the temperature of the endothermic peak appearing in the range of 750°C to 950°C in the differential thermal analysis curve of the raw material powder and a temperature 10°C higher than the temperature of the endothermic peak, and the time for heating the raw material powder at the maximum temperature is 5 hours or more and 15 hours or less.

[0008] In a third embodiment, in the first or second embodiment, the X-ray diffraction pattern obtained by powder X-ray diffraction of the raw material powder includes a peak originating from a lanthanum compound that appears in the range of 2θ from 19.38° to 21.38°.

[0009] The fourth embodiment is one in which, in any of the first to third embodiments, the solid electrolyte further comprises Sr, and the raw material powder comprises lithium carbonate. [Effects of the Invention]

[0010] According to the present invention, the infrared absorption spectrum obtained by total reflectance measurement of the raw material powder from which a solid electrolyte is synthesized by heating is obtained at wavenumber 3700 ± 10 cm⁻¹. -1 It includes a peak that appears in the range. The value obtained by dividing the absorbance of that peak by the absorbance of the peak derived from the OH of lanthanum hydroxide is 0.02 or greater. Because solid electrolytes can be synthesized at low temperatures below 1000°C, energy consumption during sintering can be reduced. The mechanism is not clear, but the wavenumber is 3700 ± 10 cm. -1 It is presumed that raw material powders containing compounds originating from peaks appearing in this range will generate a liquid phase during sintering, accelerating mass transfer. [Brief explanation of the drawing]

[0011] [Figure 1] This is a schematic diagram of the firing process in one embodiment. [Figure 2] This is a schematic diagram showing the crystal structure of a garnet-type crystal. [Figure 3] This is the temperature profile during the firing process. [Modes for carrying out the invention]

[0012] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. Figure 1 is a schematic diagram of a firing step in one embodiment. The firing step is a step of firing raw material powder of an oxide 10 in a furnace (not shown). In the present embodiment, the raw material powder 10 is accommodated in a firing jig 12 (fire-resistant container) placed on a base plate 11 of the furnace.

[0013] Examples of the furnace include a continuous firing furnace in which the base plate 11 moves through a heating zone (not shown) to convey the firing jig 12, and a batch-type firing furnace in which the base plate 11 is fixed to the furnace and the temperature around the firing jig 12 changes. Examples of the continuous firing furnace include a roller hearth kiln, a pusher kiln, a tunnel kiln, a walking beam furnace, and a mesh belt furnace. When the furnace is a mesh belt furnace, the base plate 11 may be omitted, and the firing jig 12 may be directly placed on the mesh belt to convey the firing jig 12. The solid electrolyte synthesized by firing the raw material powder 10 is an oxide having a garnet-type crystal structure containing Li, La, Zr and O. The crystal structure of the garnet-type solid electrolyte is represented by the general formula C3A2B3O 12 .

[0014] Figure 2 is a diagram schematically showing a garnet-type crystal structure. In the garnet-type crystal structure, the C-site Sc is dodecahedrally coordinated with oxygen atoms Oa, the A-site Sa is octahedrally coordinated with oxygen atoms Oa, and the B-site Sb is tetrahedrally coordinated with oxygen atoms Oa. In the garnet-type crystal structure, Li may be present at a site that is octahedrally coordinated with oxygen atoms Oa and serves as a void V. The void V is, for example, a portion sandwiched between the B-site Sb1 and the B-site Sb2. The Li present in the void V is octahedrally coordinated with the oxygen atoms Oa constituting an octahedron including the face Fb1 of the tetrahedron forming the B-site Sb1 and the face Fb2 of the tetrahedron forming the B-site Sb2.

[0015] The composition is Li7La3Zr2O 12In garnet-type solid electrolytes, La may occupy the C site (Sc), Zr may occupy the A site (Sa), and Li may occupy the B site (Sb) and the void (V). The skeletal structure of the solid electrolyte consists of a LaO8 dodecahedron, a ZrO6 octahedron, and a LiO4 tetrahedron and a LiO6 hexahedron sharing vertices or edges. The C site (La site) is substituted with Ca, Sr, Ba, etc., the A site (Zr site) is substituted with Nb, Ta, Sn, Hf, etc., and the B site (Li site) is substituted with Al, Ga, etc. The solid electrolyte can be substituted with elements according to the CSD (Cambridge Structural Database) X-ray diffraction file No. 422259 (Li7La3Zr2O 12 The diffraction angle and intensity ratio may differ compared to ).

[0016] Let's return to Figure 1 for explanation. The raw material powder 10 is exemplified by a mixture of various metal salts (starting materials) such as oxides, hydroxides, and carbonates containing Li, La, and Zr. It is possible to make part of the starting materials liquid.

[0017] There are no restrictions on the starting materials containing lithium, but lithium carbonate, lithium hydroxide, and lithium nitrate are examples. These can be used individually or in any combination of two or more in any ratio. Among these, lithium carbonate is preferred because it is easy to handle.

[0018] Lithium carbonate is preferably selected for its particle size distribution, measured by laser diffraction and scattering, which has a median diameter of 50 μm or less. The metal elements constituting the oxide's skeletal structure have electronegativity values ​​of Li=0.98, La=1.1, and Zr=1.33 (Pauling standard). Therefore, LiO4 tetrahedra and LiO6 hexahedrons have the lowest electronegativity and cannot be expected to exhibit strong covalent bonding. However, by using lithium carbonate with a median diameter of 50 μm or less, the formation of LiO4 tetrahedra and LiO6 hexahedrons can be facilitated, thereby preventing the formation of impurity phases.

[0019] Examples of starting materials containing La include lanthanum hydroxide and lanthanum carbonate. Examples of starting materials containing Zr include zirconium oxide and zirconium hydroxide. These can be used individually or in combination of two or more in any ratio. Among these, zirconium oxide is preferred because it is easy to handle.

[0020] Zirconium oxide is preferably one whose median diameter in the particle size distribution, measured by laser diffraction and scattering, is 5 μm or less. Since Zr, which constitutes the oxide's skeletal structure, has high electronegativity, relatively strong covalent bonding is expected in the ZrO6 octahedron. Using zirconium oxide with a median diameter of 5 μm or less further facilitates the formation of the ZrO6 octahedron, thereby preventing the formation of impurity phases.

[0021] The raw material powder 10 preferably contains Sr. This is because Sr substitutes La sites, elongating the crystal lattice and making it easier to establish a cubic crystal system. Examples of starting materials containing Sr include strontium carbonate, strontium hydroxide, and strontium acetate. These can be used individually or in any combination of two or more in any ratio. Among these, strontium carbonate is preferred because it is easy to handle.

[0022] The raw material powder 10 preferably contains Mg. This is because Mg, which substitutes for Li sites, eliminates lattice strain caused by electrostatic repulsion between lithium ions in the crystal lattice, making it easier to establish a cubic crystal system. Examples of starting materials containing Mg include magnesium oxide, magnesium carbonate, and magnesium hydroxide. Among these, magnesium oxide is preferred because it is easy to handle.

[0023] The raw material powder 10 is prepared so that the proportion of metal elements matches or approximates the stoichiometric composition to the extent that the desired solid electrolyte can be obtained. The raw material powder 10 may contain certain metal elements, such as lithium, that tend to evaporate and disappear during calcination, in excess of the stoichiometric composition.

[0024] The means for mixing the starting materials containing Li, La, and Zr can be either wet or dry mixing, without limitation. Wet mixing of the starting materials includes mixing the starting materials in the presence of a liquid containing water. Examples of liquids other than water include alcohols. After preparing a mixture of the starting materials by dry mixing, the mixture may be immersed in water. The liquid containing water is removed from the mixture obtained by mixing the starting materials to obtain the raw material powder 10. Examples of the raw material powder 10 include powder, and molded bodies formed by applying pressure to the powder or agglomerating the powder.

[0025] Since infrared absorption spectra show peaks at specific wavenumbers for each chemical bond, the molecular structure of the materials contained in the raw material powder 10 can be estimated from the position and intensity of the peaks in the infrared absorption spectrum of the raw material powder 10. The infrared absorption spectrum of the raw material powder 10 is measured using the total internal reflection (ATR method) method, in which a molded body (sample) of the raw material powder 10 is brought into close contact with a highly refractive material (ATR crystal) using a Fourier transform infrared spectrophotometer (FTIR), and the reflection of light that has passed through the ATR crystal at the sample surface is measured.

[0026] The infrared absorption spectrum of raw material powder 10 is wavenumber 3700 ± 10 cm⁻¹. -1 It includes a peak (hereinafter referred to as "Peak S") that appears in this range. Peak S appears at a different position from the peak (hereinafter referred to as "Peak L") that originates from the OH group of lanthanum hydroxide. Peak L is usually at wavenumber 3610±20 cm. -1 It appears within this range. The position of peak L can be confirmed by obtaining the infrared absorption spectrum of lanthanum hydroxide (reagent) alone.

[0027] The crystallographic structure of the raw material powder 10 can be determined by powder X-ray diffraction. Examples of powder X-ray diffraction conditions include: X-ray source: CuKα rays, tube voltage: 40kV, tube current: 200mA, scan speed: 10° / min, and scan step: 0.01°.

[0028] The X-ray diffraction pattern of the raw material powder 10 obtained by powder X-ray diffraction includes a peak (hereinafter referred to as "peak C") that appears in the range of 2θ 20.38°±1° (19.38°-21.38°). Peak C is not derived from lanthanum hydroxide, but is likely derived from lanthanum carbonate hydroxide LaCO3OH. Peak S included in the infrared absorption spectrum is presumed to be derived from lanthanum hydroxide compounds other than lanthanum hydroxide, such as lanthanum carbonate hydroxide. It is presumed that the starting material lanthanum hydroxide reacted with water to form the compound derived from peak S in the raw material powder 10.

[0029] The method for manufacturing a solid electrolyte includes a calcination step of raw material powder 10. The raw material powder 10 is heated in a calcination jig 12 according to a predetermined temperature profile. The calcination jig 12 includes a bottom 13 and a lid 14. The lid 14 rests on the bottom 13 on which the raw material powder 10 is placed. By covering the bottom 13 with the lid 14 during calcination, the evaporation of lithium contained in the raw material powder 10 and the incorporation of falling materials from the furnace (not shown), such as refractory materials, can be reduced. A hole 15 is provided in the lid 14 that connects the inside of the calcination jig 12 to the outside of the calcination jig 12. Gas generated by the thermal decomposition of the raw material powder 10 escapes to the outside of the calcination jig 12 through the hole 15.

[0030] Examples of materials for the firing jig 12 include inorganic materials such as alumina, cordierite, mullite, silica, magnesia, and zirconia, and metallic materials whose main component is at least one of W, Mo, and Ni. "Main component" means that the combined mass of W, Mo, and Ni is 50 wt% or more of the mass of the metallic material.

[0031] Examples of metallic materials with W as the main component include W, W-Fe alloy, W-ThO2 alloy, W-Mo alloy, W-Zr alloy, W-Ni-Cu alloy, W-Ni-Mo alloy, W-Ni-Fe alloy, W-Ni-Fe-Mo alloy, and W-Ni-Cu-Fe alloy. Examples of metallic materials with Mo as the main component include Mo, Mo-Cu alloy, Mo-Zr-Hf-C alloy, Mo-La2O3 alloy, and Mo-Re alloy. Examples of metallic materials with Ni as the main component include Ni, Ni-Cu alloy, Ni-Mo-Fe alloy, and Ni-Fe alloy.

[0032] A solid electrolyte is synthesized by solid-phase sintering of raw material powder 10 by heating. The raw material powder 10 contains a compound derived from peak S of the infrared absorption spectrum measured by total reflectance measurement, and lanthanum hydroxide derived from peak L. The absorbance of each peak, represented by the area of ​​the peak in the infrared absorption spectrum, is proportional to the concentration of the functional group corresponding to that peak. The raw material powder 10 has a value of 0.02 or higher when the absorbance of peak S is divided by the absorbance of peak L. Although the mechanism is not clear, it is presumed that when raw material powder 10 containing the required amount of compound derived from peak S is sintered, a liquid phase is generated at a low temperature of 1000°C or less, and mass transfer is promoted. This reduces the energy consumption during solid-phase sintering of the raw material powder 10.

[0033] Figure 3 shows the temperature profile 20 during the firing process. The temperature of the furnace (not shown) used to fire the raw material powder 10 is controlled according to the temperature profile 20. The furnace heats the raw material powder 10 along the temperature profile 20. The maximum temperature T of the temperature profile 20 is sufficient for the synthesis of a solid electrolyte having a garnet-type crystal structure and corresponds to the maximum temperature at which the raw material powder 10 is heated during the firing process.

[0034] The maximum temperature T is determined from the differential thermal analysis curve when the raw material powder 10 is heated. Examples of differential thermal analysis conditions include: type of atmospheric gas: Ar, atmospheric gas flow rate: 100 mL / min, and heating rate: 5°C / min. The maximum temperature T is preferably set to P ± 10°C, the temperature of the endothermic peak appearing in the 750°C to 950°C range of the differential thermal analysis curve. In this case, the maximum temperature T lies between a temperature 10°C lower than temperature P and a temperature 10°C higher than temperature P. The heating time H for the raw material powder 10 at the maximum temperature T is preferably 5 hours to 15 hours. By firing at such a temperature, the proportion of cubic crystals in the solid electrolyte (hereinafter referred to as "LLZ") having a garnet-type crystalline structure containing Li, La, Zr, and O can be increased.

[0035] The firing of the raw material powder 10 can be performed while flowing an atmospheric gas into the furnace. Examples of the atmospheric gas include air-modified gases such as purified gas obtained by removing carbon dioxide from air, inert gases such as argon and helium, neutral gases such as nitrogen and ammonia, and reducing gases such as hydrogen and carbon monoxide.

[0036] The solid electrolyte synthesized by firing can be used as a material for power storage devices such as secondary batteries and electrochemical capacitors. Examples of the electrochemical capacitor include redox capacitors utilizing redox reactions, and hybrid capacitors which are asymmetric cells combining a solid electrolyte with an electric double layer capacitor. Examples of the material for the power storage device include solid electrolyte (powder), a composite mixture of a solid electrolyte and an electrolytic solution, and a slurry containing a solid electrolyte and a dispersion medium.

Examples

[0037] The present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0038] (Example 1) (Preparation of raw material powder) The composition of the solid electrolyte is Li9Mg 0.15 La 2.75 Sr 0.25 Zr 2.10 O 12 The starting materials Li2CO3, MgO, La(OH)3, SrCO3 and ZrO2 were weighed so as to achieve the target composition. Li2CO3 was used in an excess amount in consideration of volatilization of Li during firing. The median diameter of the particle size distribution of the starting materials measured by a laser diffraction / scattering method was 5.9 μm for Li2CO3 and 0.9 μm for ZrO2. The starting materials, zirconia balls with a diameter of 3 mm and water were placed in a pot of a ball mill and wet-mixed for 60 hours to obtain a mixture. The mixture was dried until the water content became 5 wt% or less, to obtain the raw material powder in Sample I.

[0039] The composition of the solid electrolyte is Li9La 2.75 Sr 0.25 Zr 2.10 O 12The raw material powder for Sample II was obtained in the same manner as for Sample I, except that the starting materials other than MgO, Li2CO3, La(OH)3, SrCO3, and ZrO2, were weighed accordingly.

[0040] The raw material powder for Sample III was obtained in the same manner as for Sample I, except that the starting material, a 2 mm diameter zirconia ball, and water were placed in a ball mill pot and mixed wet for 20 hours.

[0041] The raw material powder for Sample IV was obtained in the same manner as for Sample I, except that the starting material, a 10 mm diameter zirconia ball, and water were placed in a ball mill pot and mixed wet for 15 hours.

[0042] The raw material powder for Sample V was obtained in the same manner as for Sample I, except that the starting material, a 3 mm diameter zirconia ball, and isopropyl alcohol were placed in a ball mill pot and mixed wet for 60 hours.

[0043] The raw material powder for Sample VI was obtained in the same manner as for Sample I, except that the starting materials were placed in a ball mill pot and mixed dry for 30 minutes.

[0044] (Infrared absorption spectrum of raw material powder) 5g of raw material powder was taken from each of samples I-VI, and a disc-shaped molded body (bulk density 2.1g / cm³) was formed using a benchtop press (uniaxial molding machine). 3 Each of the following was prepared. The infrared absorption spectrum of the molded body (raw material powder) was measured using the ATR method, and the wavenumber was 3700 ± 10 cm. -1 The absorbance of peak S appearing in the specified range was divided by the absorbance of peak L, which originates from the OH group of lanthanum hydroxide. The values ​​were 0.064, 0.064, 0.083, 0.042, 0.013, and 0.008 for samples I, II, III, IV, V, and VI, respectively. Since the values ​​for samples I-IV, where the starting material came into contact with water, were larger than those for samples V and VI, it was presumed that the compound originating from peak S was formed by the reaction of the starting material with water.

[0045] (Powder X-ray diffraction of raw material powder) The crystallographic structure of the raw material powders in samples I-IV was investigated by powder X-ray diffraction. The conditions for powder X-ray diffraction were: X-ray source: CuKα rays, tube voltage: 40kV, tube current: 200mA, scan speed: 10° / min, scan step: 0.01°. As a result of powder X-ray diffraction, samples I-IV showed peak C in the range of 2θ of 19.38°-21.38° in the X-ray diffraction pattern. Identification revealed that peak C did not originate from lanthanum hydroxide and was likely derived from lanthanum carbonate hydroxide (LaCO3OH).

[0046] (Differential thermal analysis of raw material powders) Differential thermal analysis was performed on the raw material powders in samples I-VI to measure the temperature of the endothermic peak that appeared in the range of 750°C to 950°C during heating. The conditions for differential thermal analysis were: type of ambient gas: Ar, ambient gas flow rate: 100 mL / min, heating rate: 5°C / min. The endothermic peak temperature of the raw material powders in samples I and III-VI was 845°C, and the endothermic peak temperature of the raw material powder in sample II was 873°C.

[0047] (Preparation of solid electrolytes) 5g of the raw material powder from samples I-VI was taken and molded into a disc-shaped body using a tabletop press (bulk density 2.1g / cm³). 3 Each of the following was prepared. The molded body was placed in a firing jig that included a magnesia base on which the molded body rested, and the molded body (raw material powder) was fired in a furnace (batch firing furnace) through which argon gas was flowed, raising the temperature from room temperature to a maximum temperature T (°C) at a heating rate of 100°C / hour, heating at the maximum temperature T for a time H (hours), and then cooling down at a rate of 300°C / hour according to the temperature profile.

[0048] As shown in Table 1, solid electrolytes were obtained for samples No. 1-12 by varying the type of raw material powder, the value obtained by dividing the absorbance of peak S of the raw material powder by the absorbance of peak L using the ATR method, the maximum firing temperature T, and the firing time H.

[0049] [Table 1]

[0050] (Powder X-ray diffraction of solid electrolytes) The solid electrolyte was ground in a glove box under an argon atmosphere using a mortar and pestle, and then passed through a sieve with a mesh size of 250 μm to prepare a sample for powder X-ray diffraction. After obtaining the X-ray diffraction pattern of the sample using powder X-ray diffraction with CuKα rays, the X-ray diffraction pattern was analyzed using the Rietveld method to determine the proportion of cubic crystals.

[0051] It is known that the ionic conductivity of LLZ in the cubic phase is higher than that of the tetragonal phase. Therefore, samples with a cubic phase proportion of 90 mass% (cubic:tetragonal = 90:10) or more were classified as A, samples with a cubic phase proportion of 80 mass% or more but less than 90 mass% were classified as B, and samples with a cubic phase proportion of 70 mass% or more but less than 80 mass% were classified as C. The results are shown in the crystalline phase column of Table 1.

[0052] According to Table 1, when comparing samples with a maximum temperature T of 850°C and a time H of 10 hours, the solid electrolytes in samples No. 1, 5, and 10, where the ratio of the absorbance of peak S to the absorbance of peak L of the raw material powder was 0.02 or higher, were judged as crystalline phase A, while the solid electrolytes in samples No. 11 and 12, where the ratio of the absorbance of peak S to the absorbance of peak L was less than 0.02, were judged as crystalline phase C. It became clear that cubic solid electrolytes can be synthesized at low temperatures of 1000°C or less by solid-phase sintering raw material powder with a ratio of the absorbance of peak S to the absorbance of peak L of 0.02 or higher.

[0053] Comparing samples where the absorbance of peak S divided by the absorbance of peak L was 0.064 and the time H was 10 hours, in the raw material powder group of Sample I, the solid electrolyte in Sample No. 5, with a maximum temperature T of 850°C, was judged as a crystalline phase A, while the solid electrolyte in Sample No. 2, with a maximum temperature T of 825°C, and the solid electrolyte in Sample No. 8, with a maximum temperature T of 875°C, were judged as crystalline phase C. Since the temperature of the endothermic peak in the differential thermal analysis curve of the raw material powder in Sample I is 845°C, it became clear that cubic solid electrolytes can be synthesized at low temperatures below 1000°C by setting the maximum temperature T within the range of 845±10°C.

[0054] Furthermore, the solid electrolyte in Sample No. 9, which used the raw material powder from Sample II, was classified as A in terms of its crystalline phase. Since the endothermic peak temperature in the differential thermal analysis curve of the raw material powder in Sample I was 873°C, it was revealed that a cubic solid electrolyte could be synthesized at a low temperature of 1000°C or less by setting the maximum temperature T within the range of 873±10°C. Moreover, it was revealed that the solid electrolyte (No. 5) having a garnet-type crystalline structure containing Li, La, Zr, Mg, Sr, and O could achieve a solid-phase sintering temperature approximately 25°C lower than the solid electrolyte (No. 9) having a garnet-type crystalline structure containing Li, La, Zr, Sr, and O.

[0055] Comparing samples where the absorbance of peak S divided by the absorbance of peak L was 0.064 and the maximum temperature T was 850°C, the solid electrolyte in sample No. 5 (time H 10 hours) was judged as crystalline phase A, while the solid electrolyte in sample No. 4 (time H 5 hours) and sample No. 7 (time H 15 hours) were judged as crystalline phase B. The solid electrolyte in sample No. 3 (time H 2 hours) and sample No. 7 (time H 20 hours) were judged as crystalline phase C. It became clear that the proportion of cubic solid electrolytes can be increased by setting the heating time H of the raw material powder at the maximum temperature T to between 5 hours and 15 hours.

[0056] (Example 2) (Sample No. 13) The composition of the solid electrolyte is Li 7.60 Mg 0.15 La 2.75 Sr 0.25 Zr 2.07 O 12 The starting materials Li2CO3, MgO, La2(CO3)3·8H2O, SrCO3, and ZrO2 were weighed to achieve the following ratio. An excess amount of Li2CO3 was used to account for the volatilization of Li during calcination. The median diameter of the particle size distribution of the starting materials, measured by laser diffraction and scattering, was 5.9 μm for Li2CO3 and 0.9 μm for ZrO2. The starting materials, 3 mm diameter zirconia balls, and water were placed in a ball mill pot and mixed wet for 60 hours to obtain the mixture. The mixture was dried until the moisture content was 5 wt% or less to obtain the raw material powder for sample No. 13.

[0057] (Sample No. 14) The weighed starting materials, Li2CO3 and La2(CO3)3·8H2O, along with 3mm diameter zirconia balls and water, were placed in a ball mill pot and mixed wet for 60 hours. The mixture was then dried until the moisture content was 5 wt% or less to obtain a dried product. The remaining starting materials, ethanol, and the dried product were placed in the pot and mixed wet for another 60 hours to obtain a mixture. After removing the ethanol from the mixture by water bath, the mixture was dried until the moisture content was 5 wt% or less to obtain the raw material powder for Sample No. 14 in the same manner as for Sample No. 13.

[0058] (Sample No. 15) Of the weighed starting materials, La2(CO3)3·8H2O, 3mm diameter zirconia balls, and water were placed in a ball mill pot and mixed wet for 60 hours. The mixture was then dried until the moisture content was 5 wt% or less to obtain a dried product. The remaining starting materials, ethanol, and dried product were placed in the pot and mixed wet for another 60 hours to obtain a mixture. After removing the ethanol from the mixture by water bath, the mixture was dried until the moisture content was 5 wt% or less to obtain the raw material powder for Sample No. 15 in the same manner as for Sample No. 13.

[0059] (Sample No. 16) All weighed starting materials, 3 mm diameter zirconia balls, and ethanol were placed in a ball mill pot and mixed wet for 60 hours to obtain a mixture. The raw material powder for sample No. 16 was obtained in the same manner as for sample No. 13, except that the ethanol was removed from the mixture by water bath.

[0060] (Preparation of solid electrolytes) 300g of raw material powder was taken from each of samples No. 13-16, and rectangular parallelepiped molded bodies with sides of 8cm were fabricated by uniaxial pressure of 0.02MPa. The molded bodies were placed in a firing jig including a magnesia base, and the molded bodies (raw material powder) were fired at 950°C (maximum temperature) for 10 hours in a furnace (batch firing furnace) with nitrogen gas flowing through it to obtain the solid electrolytes of samples No. 13-16.

[0061] (Powder X-ray diffraction of solid electrolytes) The solid electrolyte was ground in a glove box under an argon atmosphere using a mortar and pestle, and then passed through a sieve with a mesh size of 250 μm to prepare a sample for powder X-ray diffraction. After obtaining the X-ray diffraction pattern of the sample using powder X-ray diffraction with CuKα rays, the X-ray diffraction pattern was analyzed using the Rietveld method to determine the proportion of cubic crystals.

[0062] In samples No. 13-15, the proportion of cubic crystals in the solid electrolyte was 80 mass% or more (cubic:tetragonal = 80:20), but in sample No. 16, the proportion of cubic crystals in the solid electrolyte was less than 80 mass%.

[0063] A comparison of samples No. 13-15 and No. 16 revealed that a cubic solid electrolyte can be synthesized at a low temperature of 1000°C or less by using a starting material containing lanthanum carbonate and contacting lanthanum carbonate with water during the preparation of the raw material powder. In samples No. 13-15, the contact of lanthanum carbonate with water produces lanthanum hydroxide carbonate LaCO3OH, and it is thought that the presence of this in the raw material powder is influencing the results.

[0064] Although the present invention has been described above based on embodiments, it can be easily inferred that the present invention is not limited in any way to the above embodiments, and that various improvements and modifications are possible without departing from the spirit of the present invention. The shape and size of the firing jig 12 described in the embodiments are just examples.

[0065] In the examples, the case in which a molded body made by applying pressure to the raw material powder 10 is fired was described, but this is not necessarily the only method. It is certainly possible to fire the raw material powder 10 by placing it in a crucible or other container (firing jig). [Explanation of Symbols]

[0066] 10 Raw material powder H time T maximum temperature

Claims

1. A method for producing a solid electrolyte having a garnet-type crystalline structure containing Li, La, Zr, and O, The process includes a calcination step in which raw material powder is heated to synthesize the solid electrolyte, The aforementioned raw material powder, when its infrared absorption spectrum was measured by total internal reflection, had a wavenumber of 3700 ± 10 cm². -1 A method for producing a solid electrolyte, wherein the value obtained by dividing the absorbance of the peak appearing in the range by the absorbance of the peak originating from O-H of lanthanum hydroxide is 0.02 or greater.

2. In the firing process, the maximum temperature at which the raw material powder is heated is between a temperature 10°C lower than the temperature of the endothermic peak appearing in the differential thermal analysis curve of the raw material powder in the range of 750°C to 950°C, and a temperature 10°C higher than the temperature of the endothermic peak. The method for producing a solid electrolyte according to claim 1, wherein the time for heating the raw material powder at the maximum temperature is 5 hours or more and 15 hours or less.

3. The method for producing a solid electrolyte according to claim 1 or 2, wherein the X-ray diffraction pattern obtained by powder X-ray diffraction of the raw material powder includes a peak originating from a lanthanum compound that appears in the range of 2θ from 19.38° to 21.38°.

4. The solid electrolyte further contains Sr, The method for producing a solid electrolyte according to claim 1 or 2, comprising the raw material powder containing lithium carbonate.

Citation Information

Patent Citations

  • Garnet type ionic conductivity oxide and manufacturing method of the same

    JP2013032259A